ART OF SAFETY AUDITING a tutorial for regulators. - Andonov, Sasho ([S.l.] : CRC PRESS, 2019)
The Art of Safety Auditing: A Tutorial for Regulators provides the theory and practice of auditing safety management systems implemented by the companies in risk industries. With his extensive knowledge and experiences in quality and safety, Sasho Andonov provides the tools to fill the gap in regulatory auditing for safety management systems. The book explains in detail the overall process of auditing with emphasis on practical execution of audits by Safety Regulators in each State or International Organizations. This book presents real examples and outlines every aspect of regulations and oversight audits in high risk industries. FEATURES Offers all theoretical and practical aspects of safety audits Dedicated to regulatory bodies and companies in high risk industries Provides a holistic approach to auditing as part of regulatory oversight activities Discusses most common mistakes during audits and advices how to correct them Excellent tool for auditors and safety managers, but can be utilized in other industries
OCLC-licensed vendor bibliographic record.
Keywords: Industrial safety -- Auditing; TECHNOLOGY / Engineering / Industrial